p-Coumaric Acid Influenced Cucumber Rhizosphere Soil Microbial Communities and the Growth of Fusarium oxysporum f.sp. cucumerinum Owen - Zhou, Xingang (Public Library of Science, 2012)
BACKGROUND: Autotoxicity of cucumber root exudates or decaying residues may be the cause of the soil sickness of cucumber. However, how autotoxins affect soil microbial communities is not yet fully understood. METHODOLOGY/PRINCIPAL FINDINGS: The aims of this study were to study the effects of an artificially applied autotoxin of cucumber, p-coumaric acid, on cucumber seedling growth, rhizosphere soil microbial communities, and Fusarium oxysporum f.sp. cucumerinum Owen (a soil-borne pathogen of cucumber) growth. Abundance, structure and composition of rhizosphere bacterial and fungal communities were analyzed with real-time PCR, PCR-denaturing gradient gel electrophoresis (DGGE) and clone library methods. Soil dehydrogenase activity and microbial biomass C (MBC) were determined to indicate the activity and size of the soil microflora. Results showed that p-coumaric acid (0.1–1.0 µmol/g soil) decreased cucumber leaf area, and increased soil dehydrogenase activity, MBC and rhizosphere bacterial and fungal community abundances. p-Coumaric acid also changed the structure and composition of rhizosphere bacterial and fungal communities, with increases in the relative abundances of bacterial taxa Firmicutes, Betaproteobacteria, Gammaproteobacteria and fungal taxa Sordariomycete, Zygomycota, and decreases in the relative abundances of bacterial taxa Bacteroidetes, Deltaproteobacteria, Planctomycetes, Verrucomicrobia and fungal taxon Pezizomycete. In addition, p-coumaric acid increased Fusarium oxysporum population densities in soil. CONCLUSIONS/SIGNIFICANCE: These results indicate that p-coumaric acid may play a role in the autotoxicity of cucumber via influencing soil microbial communities.